Proposed different relay selection schemes for improving the performance of cooperative wireless networks - Dheyaa Jasim Kadhim; Saba Qasim Jabbar (Universitas Ahmad Dahlan, 2021)
Relay selection is a new method currently used to develop and improve cooperative wireless networks. One of the main advantages of this new technology is that it can achieve cooperative diversity gain without installing multiple antennas in the transmitter or receiver. Relay selection algorithms can be used to select one node to become a relay node from a set of N candidate relays with optimization criteria as the outage probability or frame error rate. The selection process is preferable to operate in a distributed fashion and offers only reasonable costs in terms of manufacturing complexity and flexible handling over wireless cooperative networks. In this work, different relay selection schemes are proposed to enhance the cooperative wireless networks in terms of different approaches including: 1) Relay selection-based destination feedback scheme, 2) Relay selection based a ready-to-send/clear-to-send (RTS/CTS) messages scheme, 3) Relay selection-based identification messages (IDM) table scheme, and 4) Relay selection-based relay power consuming scheme. The experimental results via suggested case study show that the performance of overall cooperative network is enhanced in terms of increasing throughput, energy saving (efficiency maximization), blocking reduction and outage reduction (PER minimization).